2020
DOI: 10.1002/aqc.3300
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal fishing activities and their documented interactions with juvenile white sharks inside a nursery area

Abstract: Juvenile white sharks distribute in coastal nursery areas, which are essential for population growth. Bahía Sebastián Vizcaíno (BSV), Mexico, is a white shark nursery area in the north‐eastern Pacific. Despite existing regulations forbidding the capture of white sharks, incidental catches still occur in some areas. Artisanal fisheries constitute one of the most important economic activities in BSV, yet no formal description of either these fisheries or the incidental catch of juvenile white sharks exists due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Previous studies that have addressed YOY white sharks from this Northeast Pacific population have identified the SCB as an important resource that provides nursery habitat for these sharks, and that habitat selection is driven by temperature, depth, and distance to shore (Klimley, 1985;Dewar et al, 2004;Weng et al, 2007b;Lowe et al, 2012;Lyons et al, 2013;White et al, 2019). However, the geographic range of YOYs and juveniles of this population extends to at least the southern tip of Baja California ∼1200 km (Weng et al, 2012), with specific nursery habitat identified toward the southern extent of the latitudinal range of this population, in Bahía de Sebastián Vizcaíno, Mexico (Oñate-González et al, 2017;Tamburin et al, 2019;García-Rodríguez and Sosa-Nishizaki, 2020). These studies, based upon data derived from satellite telemetry, remote sensing, and fisheries interactions, have been restricted to broad-scale observations of environmental drivers of habitat use and selection.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies that have addressed YOY white sharks from this Northeast Pacific population have identified the SCB as an important resource that provides nursery habitat for these sharks, and that habitat selection is driven by temperature, depth, and distance to shore (Klimley, 1985;Dewar et al, 2004;Weng et al, 2007b;Lowe et al, 2012;Lyons et al, 2013;White et al, 2019). However, the geographic range of YOYs and juveniles of this population extends to at least the southern tip of Baja California ∼1200 km (Weng et al, 2012), with specific nursery habitat identified toward the southern extent of the latitudinal range of this population, in Bahía de Sebastián Vizcaíno, Mexico (Oñate-González et al, 2017;Tamburin et al, 2019;García-Rodríguez and Sosa-Nishizaki, 2020). These studies, based upon data derived from satellite telemetry, remote sensing, and fisheries interactions, have been restricted to broad-scale observations of environmental drivers of habitat use and selection.…”
Section: Discussionmentioning
confidence: 96%
“…their stomach contents (Santana-Morales et al, 2012;García-Rodríguez and Sosa-Nishizaki, 2020). Hence, demersal prey may not have been fully representative of the shark's food sources.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are caught incidentally in the nearshore areas of BSV as well as within Ojo de Liebre Lagoon (OLL), a semi-enclosed hypersaline shallow estuary located within the bay system (García-Rodríguez and Sosa-Nishizaki, 2020). These catches occur when local artisanal fishers target high-value species that are part of the white shark's diet (Santana-Morales et al, 2012;García-Rodríguez and Sosa-Nishizaki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, prohibition of white shark catch (DOF, 2007(DOF, , 2014 has made the targeted fishery clandestine, not inactive. Increased enforcement has been a challenge in the Gulf, making monitoring, data collection, and enforcement difficult (Ainsworth et al, 2012;Cinti et al, 2010;García-Rodríguez & Sosa-Nishizaki, 2020;Hernandez & Kempton, 2003;Lluch-Cota et al, 2007); regular monitoring with fishermen involvement may improve conservation efforts (García-Rodríguez & Sosa-Nishizaki, 2020). Based on effective gillnet restrictions off California (Lowe et al, 2012), gear modifications or restrictions may reduce white shark bycatch (García-Rodríguez & Sosa-Nishizaki, 2020), while allowing adaptable artisanal fishers to utilize alternative gear and/or adjacent regions.…”
Section: F I G U R Ementioning
confidence: 99%
“…White shark-specific legislation has moved from a listing as "threatened" (DOF, 2002), to illegal targeting/trade (DOF, 2007), to illegal possession and mandatory release of incidental catch (DOF, 2014). Lack of reporting and monitoring is an ongoing challenge (Arreguín-Sánchez & Arcos-Huitrón, 2007;Cisneros-Montemayor et al, 2013;García-Rodríguez & Sosa-Nishizaki, 2020;Hernandez & Kempton, 2003), and incidental catch still occurs in American and Mexican fisheries (Oñate-González et al, 2017). A recent white shark status review under the Endangered Species Act by the National Oceanic & Atmospheric Administration (NOAA) (Dewar et al, 2013) recognized that additional mortality of adult females may occur in the Gulf, but at uncertain levels (García-Rodríguez & Sosa-Nishizaki, 2020) which precludes incorporation in population assessments.…”
mentioning
confidence: 99%